1993
DOI: 10.1126/science.8395079
|View full text |Cite
|
Sign up to set email alerts
|

Repair of DNA Methylphosphotriesters Through a Metalloactivated Cysteine Nucleophile

Abstract: The Escherichia coli Ada protein repairs methylphosphotriesters in DNA by direct, irreversible methyl transfer to one of its own cysteines. Upon methyl transfer, Ada acquires the ability to bind specific DNA sequences and thereby to induce genes that confer resistance to methylating agents. The amino-terminal domain of Ada, which comprises the methylphosphotriester repair and sequence-specific DNA binding elements, contains a tightly bound zinc ion. Analysis of the zinc binding site by cadmium-113 nuclear magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
179
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(185 citation statements)
references
References 24 publications
6
179
0
Order By: Relevance
“…The resulting Cd(II)-substituted N-Ada retained the ability to repair S p -methylphosphotriester, but the rate was one-fourth that of the native Zn(II)-containing protein. 46 This experiment suggested that metal is directly involved in the rate-determining step of the repair. To determine the ligands around the metal ion, 113 Cd-substituted N-Ada20 was prepared for 113 Cd nuclear magnetic resonance (NMR) investigations.…”
Section: N-ada Utilizes a Zinc(ii)-activated Cysmentioning
confidence: 99%
“…The resulting Cd(II)-substituted N-Ada retained the ability to repair S p -methylphosphotriester, but the rate was one-fourth that of the native Zn(II)-containing protein. 46 This experiment suggested that metal is directly involved in the rate-determining step of the repair. To determine the ligands around the metal ion, 113 Cd-substituted N-Ada20 was prepared for 113 Cd nuclear magnetic resonance (NMR) investigations.…”
Section: N-ada Utilizes a Zinc(ii)-activated Cysmentioning
confidence: 99%
“…EaCoMT belongs to a subset of the family of alkyl transferases for which zinc is crucial in activation of a thiol for nucleophilic attack (17,42). Other examples of this family are the Ada protein, which is involved in DNA repair (44,45), betaine:homocysteine methyltransferase (10), cobalamin-independent methionine synthases (MetE) (24,42), and various methanogenic methyltransferases (MtaA, MtbA, and MtsA) (56).…”
Section: Eacomt: Zinc-mediated Activation Of the Com Thiol Reactions mentioning
confidence: 99%
“…The Ada protein removes methyl groups from the premutagenic lesions 06-methylguanine and 04-methylthymine, transferring them irreversibly to Cys-321, a cysteine located in its carboxylterminal domain (4-6), and also removes methyl groups from the S diastereoisomers of DNA methylphosphotriesters, transferring them irreversibly to Cys-69, which is located in its amino-terminal domain (7-10). Methylation at Cys-69 converts Ada into a strong transcriptional activator ofits own gene (ada) and also of several other genes (alkB, alkA, and aidW) (11)(12)(13)(14)(15) N-methyl-N'-nitro-N-nitrosoguanidine. …”
mentioning
confidence: 99%